PENGATURAN PENYIDIKAN TERHADAP ANGGOTA KEPOLISIAN REPUBLIK INDONESIA YANG MELAKUKAN TINDAK PIDANA - Nainggolan, Dedi Ardianto; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The probe is an early stage of the criminal law enforcement process or the working of the Criminal Justice System. The probe has a position and role are very important and strategic to determine the success or failure of subsequent criminal law enforcement process. Implementation of good investigation will determine the success of the Public Prosecutor in the prosecution and then makes it easy for judges to explore / discover the truth materially examine and prosecute in court. Many obstacles and barriers, of legislation and the implementation of a technical field such as the behavior of law enforcement officials and community participation led to many legal inequality that occurred within the police force, which on the one hand they are as investigator and on the other side of them as perpetrators of crime should be investigated. Investigations conducted by members of the police against fellow members of the police tends not professional and their reluctance to investigate a fellow of the institution.The purpose of this thesis are: First, to find out the settings investigations against members of the Indonesian National Police for a criminal offense; Second, to determine the ideal setting investigation against members of the Indonesian National Police for a criminal offense. This type of research used in this study, using normative legal research can also be called by the doctrinal legal research. In this normative legal study conceptualized as what is written in the legislation (law in books).According to Article 1 paragraph 1 of the Law of Criminal Procedure and Article 1 point 10 of Law Number 2 of 2002 on the Indonesian National Police, that is the investigation of a series of actions the investigator in the case and in the manner set forth in this law to find and collect evidence with evidence with evidence that shed light on the crime happened and to find the suspects. Whereas Article 1 point 1 and 2 of the Code of Criminal Procedure states that the investigator is an official police or specific civil Servants specifically authorized by law. To overcome the obstacles Police in investigating the need to establish an institution for external police who can supervise and follow up members of the police who committed the crime and reforming the Code of Criminal Procedure which governs the investigator, the processes of investigation and control of fossil or cooperation between investigators and other law enforcement officials.Keywords: Investigation setting-Police-Crime